(G, [STIX]x1D707)-DISPLAYS AND RAPOPORT–ZINK SPACES. (19th July 2020) - Bültel, O.; Pappas, G.
Abstract : Let (G, [STIX]x1D707) be a pair of a reductive group G over the p -adic integers and a minuscule cocharacter [STIX]x1D707 of G defined over an unramified extension. We introduce and study ' (G, [STIX]x1D707) -displays' which generalize Zink's Witt vector displays. We use these to define certain Rapoport–Zink formal schemes purely group theoretically, i.e. without p -divisible groups.